Responses of Eleventh Grade Students to the Gamified ZEP QUIZ in Teaching Reading Comprehension: A Quantitative Inquiry - Yudith Septrianto; Suhartono Suhartono; Ahmad Munir (Journal of General Education and Humanities, 2026)
Reading comprehension remains a challenge for many vocational high school students, particularly due to low motivation to learn and limited engagement in digital learning environments. In response to this issue, gamification has emerged as a potential strategy to enhance students’ participation and learning experiences. Therefore, this study aimed to evaluate eleventh-grade students’ responses toward the implementation of the ZEP QUIZ gamification platform in teaching reading comprehension. The research employed a descriptive, quantitative design using a single-point survey. Data were collected through a Likert-scale questionnaire administered to eleventh-grade students at a vocational high school and analyzed descriptively to identify students’ perceptions of the platform. The findings revealed that students demonstrated highly positive responses regarding motivation, engagement, and ease of use. The gamified features of ZEP QUIZ, particularly leaderboards and timers, were perceived as effective in increasing students’ focus, participation, and interest in comprehending argumentative texts. Overall, the results indicate that ZEP QUIZ provides an engaging and supportive learning environment that enhances students’ reading comprehension experiences in English language learning. The study concludes that ZEP QUIZ is an effective gamification-based instructional tool for improving student engagement and fostering positive learning experiences in vocational education.